(untitled) - Wilcox, Pamela J. (Hoboken, N.J., 2006)
Exposing the Elephants takes an honest look at the fundamental obstacles facing the nonprofit sector, with topics including: The Wide Reach of Nonprofits; The Role of Nonprofits; Myths That Surround Nonprofits; Rating Nonprofit Performance; The Five Elephants of the Nonprofit Industry; "Live Lessons" and "At the Salt Mines"—mini- dramas demonstrating the challenging situations that arise within a nonprofit—and the tools and techniques to bring about real change
Keywords: Nonprofit organizations,Các tổ chức phi lợi nhuận; Management,Quản lý